A Trust-Based Algorithm to Secure Transmission in MANET - Agrawal, Ankit (My University, 2016)
A mobile ad hoc network (MANET) is made up of various mobile nodes defined as free to move anywhere in the network and they communicate with each other wirelessly. MANET is an infrastructure-less network and is also self organized network, where nodes are responsible for every operation performed by them and responsible for their maintenance. Due to the dynamic nature of MANET nodes, they are exposed to various security attacks. To increase the security in MANET, it is vital to evaluate the node’s trustworthiness in the network. Trust and reputation based approaches provides an effective and efficient way to identify selfish and malicious nodes in the network. In trust based schemes, each node calculates the trust of other nodes either direct or indirect trust based information. Routing path is measured with the help of the calculated trust values. It is necessary to use the routing mechanism for transferring the packets from source to destination node. Source node needs to find the packet delivery route before sending the data packets. The route must be trusted from source to destination node. So, the most important task in any kind of routing algorithm is to select the secured/trusted path. We propose a trust-based algorithm to select the most trusted path among all possible paths from source to destination node. Trust-based scheme is considered while designing the algorithm. In the proposed algorithm, trust values are assumed among two nodes in the scale of 1 to 10. The proposed algorithm is implemented in JAVA programming language and the results show direct towards the most secured path based on the trust value.
Keywords: MANET; Security; Trust Management; Most Trusted Path